Pedagogical Aspects Of Forming The Education Of Musical Culture In Youth Students - Fayzullayev, Ermat Majidovich (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2025)
One of the main tasks of musical education is to form a modern musical culture. In order to play modern music, one must know, be able to listen to, and perceive it, and at the same time master modern performance techniques. In this regard, the responsibility of teachers is very high, they must not only teach what they know, but also be well versed in the trends and ideological directions of modern music. A teacher-musician must also be a performer. The theory of education separated from live music makes no sense.